LC3-Mediated Mitophagy After CCCP or Vibrio splendidus Exposure in the Pacific Oyster Crassostrea gigas - Sun, Jiejie; Lv, Xiaoqian; Leng, Jinyuan; Wang, Lingling; Song, Linsheng (Frontiers in Cell and Developmental Biology, 2022)
Mitochondrial selective autophagy, known as mitophagy, surveils the mitochondrial population by eliminating superfluous and/or impaired organelles to mediate cellular survival and viability in response to injury/trauma and infection. In this study, the components of the mitophagy pathway in the Pacific oyster Crassostrea gigas were screened from NCBI with reference to the protein sequences of the human mitophagy process. A total of 10 mitophagy process–related genes were identified from C. gigas, including NIX, FUNDC1, PHB2, Cardiolipin, P62, VDAC2, MFN2, PARL, MPP, and OPTN. They shared high similarities with their homologs in the human mitophagy pathway and were expressed in various tissues of C. gigas. After CCCP exposure, the fluorescence intensity of the mitochondrial probe JC-1 monomers increased significantly in hemocytes, while the fluorescence intensity of JC-1 aggregates decreased significantly. Meanwhile, the fluorescence of lysosomes was found to be co-localized with that of CgLC3 and mitochondria in CCCP-treated hemocytes. Double- and single-membrane-bound vacuoles resembling autophagic structures were observed in the hemocytes after CCCP exposure. The fluorescence intensity of JC-1 monomers and the abundance of CgLC3Ⅱ in hemocytes both increased after Vibrio splendidus exposure. At the same time, the green signals of CgLC3 were co-localized with red signals of the mitochondria, and the fluorescence intensity of autophagy increased significantly in hemocytes after V. splendidus exposure. The results confirmed the existence of a complete mitophagy pathway in mollusks for the first time, which was helpful for further study on the function of mitochondrial autophagy in mollusks.